1997
DOI: 10.1007/pl00005071
|View full text |Cite
|
Sign up to set email alerts
|

Activity of glibenclamide-sensitive K+ channels under unstimulated conditions in smooth muscle cells of pig proximal urethra

Abstract: The membrane potential in pig proximal urethra was examined by use of the microelectrode technique. In cells 1-2 cm from the bladder neck the membrane potential was quiescent, with a value of -37.2+/-2.5 mV (n = 16). In some cells small spontaneous de- and hyperpolarizations were seen. Glibenclamide (1 microM) caused a small but significant depolarization in tissue strips (12+/-3 mV, n = 3) and also in dispersed cells using whole-cell patch electrodes (13+/-3 mV, n = 5). In the conventional whole-cell voltage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…Our results suggest that this is not the case in rat mesenteric small arteries at high concentrations of nicorandil, since K + current activation by 300 mM nicorandil was una ected by inhibition of GC with LY 83583 (Figure 3). Similarly, in pig urethra, Teramoto & Brading (1997) found that methylene blue did not a ect channel activation by nicorandil. Relaxations to nicorandil at concentrations below 300 mM, however, were almost completely inhibited by a high concentration of LY 83583 (10 mM, Figure 7a).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 88%
See 3 more Smart Citations
“…Our results suggest that this is not the case in rat mesenteric small arteries at high concentrations of nicorandil, since K + current activation by 300 mM nicorandil was una ected by inhibition of GC with LY 83583 (Figure 3). Similarly, in pig urethra, Teramoto & Brading (1997) found that methylene blue did not a ect channel activation by nicorandil. Relaxations to nicorandil at concentrations below 300 mM, however, were almost completely inhibited by a high concentration of LY 83583 (10 mM, Figure 7a).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 88%
“…In rabbit portal vein, the channel activated may have a slightly lower conductance of 26 pS (Kamouchi & Kitamura, 1994), though a higher conductance channel has also been reported to be activated by another K ATP channel opener, pinacidil, in this tissue (50 pS, Kajioka et al, 1991). In cells from pig urethra, Teramoto & Brading (1997) found that nicorandil activated a glibenclamide-sensitive channel with a somewhat larger conductance, 43 pS in symmetrical high [K + ]. The channels activated by nicorandil and other K ATP channel openers have often been found to also be susceptible to activation by intracellular nucleoside diphosphates (Kamouchi & Kitamura, 1994;Teramoto & Brading, 1997).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 99%
See 2 more Smart Citations
“…This might provide useful information for the synthesis of novel types of K þ channel opener and mefenamic acid may serve as a useful prototype for designing more selective compounds for K ATP channels as well as BK Ca channel openers. Since these channels can be activated under normal physiological conditions around the resting membrane potential (Teramoto et al, 1997), they represent a significant target for the treatment of various urinary tract dysfunctions such as urge incontinence in urinary bladder and bladder outflow obstruction in urethra.…”
Section: Clinical Implication and Good Clues For Synthesizing Novel Tmentioning
confidence: 99%